Ascaris lumbricoides: prevalence and associated factors among pre-school children in Rukiga district, Uganda: a cross-sectional study - Martine Kasiita; Stephen Businge; Agnes Napyo; James K. Tumwine (BMC Infectious Diseases)
Abstract Background Ascaris lumbricoides infestation remains a public health problem worldwide. It mainly affects children resulting into undernutrition, impaired growth and physical development, intestinal obstruction and death. We aimed to determine the prevalence and factors associated with Ascaris lumbricoides infestation among children aged 6–59 months in Rukiga district, Uganda. Methods In this cross-sectional study, we recruited 739 children aged 6–59 months and their caregivers between September and October 2023. Semi-structured questionnaires were used to collect data on sociodemographic characteristics of the caregivers. We examined children’s stool for Ascaris lumbricoides ova using the Kato-Katz method. We estimated adjusted odds ratios using multivariable logistic regression to determine the factors associated with Ascaris lumbricoides infestation. Results The prevalence of Ascaris lumbricoides infestation was 2.7% (n = 20/739), (95% CI. 1.7–4.1). Factors associated with Ascaris lumbricoides infestation were: Child-related characteristics including: the child having not been dewormed 6 months prior to the study (AOR 2.04, 95% CI: 1.04–4). Household characteristics including: disposal of child’s stool in the compound/ garden (AOR 12.53, 95% CI: 3.44–45.64), if there are more than two children under 5 years living in the household (AOR 0.24, 95% CI: 0.11–0.52). Care-giver characteristics including the primary caregiver being: the father (AOR 6.09, 95% CI: 1.21–30.61), a Christian (AOR 0.04, 95% CI: 0.01–0.17). Conclusion and recommendations Ascaris lumbricoides infestation was 2.7% among preschool children. We recommend the inclusion of male partners in health interventions targeting children under the age of five years especially the immunization programs. Community health programs should consider targeted messages in health education campaigns especially the handling and disposal of feces and the importance of deworming children. The association between religion and Ascaris lumbricoides infestation needs further studies.